Exploration of different solid variants of the anticancer medication Panobinostat (PNB) with improved physicochemical attributes - Kenguva, Gowtham; Giri, Lopamudra; Rout, Smruti Rekha; Acharya, Achyuta Nanda; Dandela, Rambabu (Journal of Molecular Structure, 2023)
Panobinostat (PNB), is a medication used for the treatment of multiple myeloma. It is a BCS Class II drug with strong permeability and poor solubility. Therefore, it is highly desirable to investigate novel PNB variants with improved physiochemical properties. In this regard, several solid forms of PNB have been produced employing mechanochemistry and solution crystallisation techniques using a variety of GRAS (Generally Recognized as Safe) salt formers, notably oxalic acid (OA), fumaric acid (FA), maleic acid (MA), and succinic acid (SA). Powder X-Ray Diffraction (PXRD), Single Crystal X-Ray Diffraction (SCXRD), and thermal analysis such as Thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC) were used to characterize all the synthesised molecular adducts. Hirshfeld surfaces and fingerprint plots demonstrate that the molecular entities are stabilized by O & BULL;& BULL;& BULL;H, C & BULL;& BULL;& BULL;H, C & BULL;& BULL;& BULL;C and H & BULL;& BULL;& BULL;H intermolecular interactions. Moreover, the solubility of parent PNB and its molecular adducts in pH 1.2/pH 6.8 was evaluated at room temperature. In every instance, an increase in the solubility of molecular salts relative to the parent medication is seen, notably PNB.MA exhibits enhanced solubility of 0.294 mg/ml, a 73fold increase over the parent PNB. Furthermore, it is observed that this upsurge in solubility of all the forms is static at pH 1.2. A thorough analysis of the recovered residue after solubility showed that most of the molecular adducts were stable at pH 6.8 and did not display any phase change or dissociation (with the exception of PNB.MA), but at pH 1.2 they transferred into a new stable form and extensive analysis confirmed that it converted into PNB.Cl salt. To the best of our knowledge, this is the first report on novel solid forms of PNB with enhanced physicochemical properties which implies that the obtained PNB molecular adduct may help in the development of improved PNB formulations.
Keywords: Hydrogen bond; Molecular adducts; solubility; Solvates

New binary adducts of panobinostat with different carboxylic acid based NSAIDs: structural analysis and physicochemical properties investigation - Kenguva, Gowtham; Rout, Smruti Rekha; Kar, Ananya; Giri, Lopamudra; Shaikh, Tabrez R.; Jadab, Madhusmita; Pal, Satyanarayan; Dandela, Rambabu (ChemistrySelect, 2024)
Adoption of multitarget, cost-effective fixed-dose medication combinations can help lower the pill load without increasing the risk of adverse events. In this study, three new 1:1 drug-drug binary solid forms of panobinostat (PNB) and nonsteroidal anti-inflammatory drugs (NSAIDs) were effectively synthesized by liquid-assisted grinding and slow evaporation crystallization techniques. The obtained solid forms were extensively characterized by various analytical techniques. The structural investigation revealed that all molecular adducts formed salt with a comparable R42\${\textbackslashmathrm{R}}_4<\^>2\$(10) graph set pattern created by heteromeric interactions formed between PNB and corresponding salt formers. To determine the dissolving behavior of the newly developed adducts, solubility tests were performed at various pH levels (pH 1.2 and pH 7), and the results indicated that the solubility of all forms is increased at pH 7.0, particularly PNB.NIF has a solubility of 0.195 mg/mL, which is seven times higher than the parent drug. Furthermore, PXRD was used to assess the stability of the synthesized adduct at varied temperature and humidity levels and it was found that all the adducts are stable. Based on the findings, we hope that the newly found PNB drug-drug binary adducts have possible potential to broaden the use of drug combinations without changing the chemical structures.
Keywords: Drug-drug salts; Heteromeric interactions; Hydrogen bond; Non-steroidal anti-inflammatory drugs; Panobinostat

Novel molecular adducts of an anti-cancer drug vandetanib with enhanced solubility - Bandaru, Ravi Kumar; Giri, Lopamudra; Krishna, Gamidi Rama; Dandela, Rambabu (Crystengcomm, 2024)
The solubility, permeability, and dissolution rate of an active pharmaceutical ingredient (API) are critical factors in determining its pharmacokinetic performance in oral dosage forms. Modifying these properties can potentially enhance the drug's pharmacokinetics. Vandetanib (VDTB), classified as a class II anti-cancer drug in the biopharmaceutical classification system (BCS), suffers from low solubility (0.008 mg mL-1) and an extended pharmacokinetic half-life (19 days), necessitating the administration of high doses, which leads to undesirable side effects. To address this issue, we have employed a crystal engineering approach to enhance the solubility of VDTB. We employed the liquid-assisted grinding (LAG) method followed by the slow evaporation technique to prepare novel solid forms of VDTB by incorporating various aliphatic dicarboxylic acids, including succinic acid (SUA), adipic acid (ADA), pimelic acid (PIA), azelaic acid (AZA), and sebacic acid (SBA). These newly obtained solid forms were characterized by SC-XRD, PXRD, TGA, and DSC experiments. The crystal structure analyses revealed a proton transfer between the carboxylic acid group of aliphatic acids and the N-methyl piperidine moiety of VDTB, confirming salt/adduct formation. Additionally, all of the molecular salts were stabilized by charge-assisted N+-HMIDLINE HORIZONTAL ELLIPSISO- hydrogen bonds, while the parent VDTB crystal structure is stabilised by N-HMIDLINE HORIZONTAL ELLIPSISN interactions. Moreover, the solubility and dissolution rate of these new solid forms were assessed in a pH 7.4 phosphate buffer medium, with the results indicating that all of the solid forms, except for VDTB:SBA, exhibited higher solubility compared to pure VDTB. These findings offer promising prospects for the development of an improved VDTB formulation with enhanced pharmacokinetic properties. Successful attempt to improve the solubility and dissolution rate of Vandetanib - an anti-cancer drug, by crystal engineering approach.
Keywords: Amorfization; hydrate; Parameters; Salt; Thyroid-Cancer

Synthesis, characterization and theoretical investigations of the newly developed molecular salts of an anti-psychotic drug (Penfluridol) - Kenguva, Gowtham; Rout, Smruti Rekha; Kar, Ananya; Giri, Lopamudra; Mahapatra, Sanat Kumar; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Dandela, Rambabu (Journal of Molecular Structure, 2025)
Penfluridol (PEN) is a clinically relevant antipsychotic medication used to treat schizophrenia; nevertheless, its bioavailability is limited due to its poor solubility. To address this issues, new molecular salts of PEN are being produced utilizing an array of GRAS (Generally Recognised AS Safe) salt formers such as oxalic acid (OXA), malonic acid (MAL), maleic acid (MAE), and an artificial sweetener (saccharin (SAC)). A variety of solid-state analytical techniques were used to identify and characterize the resulting molecular salts. Moreover, PEN and its novel salts' solubility were assessed using high-performance liquid chromatography (HPLC) and the data revealed that among all the adducts PEN.MAL exhibited a significantly higher solubility which is similar to 15 times more than the parent drug PEN. Furthermore, in order to enhance comprehension of the hydrogen bonding interaction, the Hirshfeld surface (HS), frontier molecular orbital (HOMO-LUMO), non-covalent interaction plots (NCIs), and electrostatic potential maps (ESP) investigations are discussed. Additionally, the stability of the synthesized adducts was evaluated over a 2-week period under accelerated humidity (90 % +/- 5 % RH, 40 +/- 1 degrees C) and it was observed that all the adducts demonstrated excellent stability. In light of the aforementioned observations, we expect that the latest discovery will be a superior alternative for refining and strengthening the pharmacological features of PEN.
Keywords: Anti-psychotic drug; Hydrogen bond; Liquid-assisted grinding (LAG); solubility